Nephrologists' management of patient medications in kidney transplantation: results of an online survey. Issue 5 (17th June 2015) - Crawford, Kimberley; Low, Jac Kee; Manias, Elizabeth; Walker, Rowan; Toussaint, Nigel D.; Mulley, William; Dooley, Michael; Ierino, Francesco L.; Hughes, Peter; Goodman, David J.; Williams, Allison
Abstract Rationale, aims and objectives Medication adherence is essential in kidney transplant recipients to reduce the risk of rejection and subsequent allograft loss. The aim of this study was to delineate what 'usual care' entails, in relation to medication management, for adult kidney transplant recipients. Methods An online survey was developed to explore how nephrologists promote and assess medication adherence, the management of prescriptions, the frequency of clinic appointments and the frequency of clinical screening tests. Nephrologists from all acute kidney transplant units in Victoria, Australia, were invited to participate. Data were collected between May and June 2014. Results Of 60 nephrologists invited to participate, 22 completed the survey (response rate of 36.6%). Respondents had a mean age of 49.1 ± 10.1 years, with a mean of 20.1 ± 9.9 years working in nephrology and 14 were men. Descriptive analysis of responses showed that nephrologists performed frequent screening for kidney graft dysfunction that may indicate medication non‐adherence, maintained regular transplant clinic visits with patients and emphasized the importance of medication education. However, time constraints during consultations impacted on extensive patient education and the long‐term medication follow‐up support was often delivered by the renal transplant nurse coordinator or pharmacist. Conclusions This study highlighted that nephrologists took an active approach in the medication management of kidney transplant recipients, which may assist with facilitating long‐term graft survival. Ultimately, promoting medication adherence needs to be patient centred, involving an interdisciplinary team of nephrologists, pharmacists and renal transplant nurse coordinators, working together with the patient to establish optimal adherence.